Whey protein and its application to human - K.H. Khan2*, Aniruddha Bhati1 (Journal of Experimental Sciences, 2010)
Proteins are complex macromolecules made up of amino acid which is essential for the biological activities. The coagulation of milk creates whey protein having the high nutritional value. This article discusses and summarizes important work in literature in response to the composition and production of whey protein. In this communication we reviewed the medicinal value of whey in various diseases like cancer, hepatitis, HIV and cardiovascular diseases. The role of whey protein in blood pressure and inflammatory response were also discussed. Its significance in human health particularly in sport performance was highlighted. Much stress was given to explain its role on satiety, adiposity and general health. Morever biotechnological prospective of whey protein was also explained. This article will be helpful for the biotechnologist working in the field of dairy which finally affects the human health.